Occult hepatitis C virus infection in patients with beta‐thalassemia major: Is it a neglected and unexplained phenomenon?. Issue 7 (18th February 2019) - Ayadi, Ahmad; Nafari, Amir Hossein; Irani, Shiva; Mohebbi, Elham; Mohebbi, Fahimeh; Sakhaee, Fatemeh; Vaziri, Farzam; Siadat, Seyed Davar; Fateh, Abolfazl
Abstract: Occult hepatitis C virus (HCV) infection (OCI) is described as the presence of viral genome in both hepatocytes and peripheral blood mononuclear cells (PBMCs) despite constant negative results on serum HCV RNA tests. Beta‐thalassemia major (BTM) describes a group of inherited blood diseases. Patients with BTM require repeated blood transfusions, increasing the risk of exposure to infectious agents. We aimed to assess the prevalence of OCI in Iranian BTM patients and to identify the role of host factors in OCI positivity. A total of 181 BTM patients with HCV negative markers were selected. HCV RNA was tested in PBMCs using nested polymerase chain reaction assay. The positive samples were then genotyped via restriction fragment‐length polymorphism (RFLP) and 5′‐untranslated region sequencing. Six (3.3%) out of 181 BTM patients had viral HCV genomes in PBMC samples. Three (50.0%), two (33.3%), and one (16.7%) out of these six patients were infected with HCV‐1b, HCV‐1a, and HCV‐3a, respectively. OCI positivity was significantly associated with the serum level of uric acid ( P = 0.045) and ABO blood group ( P = 0.032). Also, OCI patients had unfavorable IFNL3 rs12979860 TT, IFNL3 rs8099917 GG, IFNL3 rs12980275 GG, and IFNL4 ss469415590 ∆G/∆G genotypes. In conclusion, we indicated the low frequency of OCI in BTM patients. Nevertheless, more attention is warranted considering the importance of this infection. Also, further studies are necessary to determine the actual prevalence of OCI among BTM patients in Iran.